Burnout among catholic priests in Brazil: prevalence and associated factors - Dias, Rosimar José de Lima (Interação em Psicologia, 2019)
Catholic priests experience a myriad of stressors in their pastoral work, face countless demands and unrealistic expectations, are under constant scrutiny, and are surrounded by a culture that is increasingly secular and apparently less supportive. Consequently, priests may experience significant levels of burnout, which is characterized as a syndrome resulted from inadequate responses to chronic emotional stress. The purpose of this cross-sectional research was to investigate the rates of burnout among Catholic clergy in Brazil and associated factors. Randomly selected Catholic priests in Brazil (N = 242) were given the Maslach Burnout Inventory (MBI), a sociodemographic questionnaire, and several survey items to assess psychosocial and spiritual variables. Results indicated that approximately one third of priests in Brazil experience moderate to high burnout rates. Younger priests reported higher levels of burnout. Vocational satisfaction, social support, self-care, and spiritual practices were significantly correlated to lower levels of burnout. In consistency with the literature on clergy burnout, these findings suggest that these factors may have a buffering effect on burnout among priests. In conclusion, there is a significant number of priests in Brazil feeling overwhelmed and experiencing clinically significant burnout levels. This is a problem that has to be taken seriously and requires immediate attention.